A Study on Professors’ Adeptness and Students’ Expectations on Perceived Student Learning Outcomes - Prathiba, Srividya (Prabandhan: Indian Journal of Management, 2020)
Higher education plays a major role in defining the education system in India. This paper aimed at devising a structural equation model on professors’ adeptness, students’ expectations, and student perceived learning outcomes among engineering college students studying in Chennai. The study analyzed the impact of faculty performance and studentsâ€™ expectations on perceived performance of the students. A structured questionnaire was administered for gathering the data. Primary data were collected from 250 engineering college students in Chennai. Exploratory factor analysis and confirmatory factor analysis were used to identify the various faculty performance factors, studentsâ€™ expectations, and their effect on studentsâ€™ performance. The results suggested that faculty behaviors and attitudes affect students profoundly, which in turn suggests that teachers play the single-most important role in student learning outcomes.